Public Policy Challenges in Ghana - Essuman, Bismark (My University, 2022)
More often than not, those in positions of power believe that, regardless of their likelihood of success, policies should be energetically pursued if they have the support of the majority. Since Ghana's independence, numerous administrations, both previous and current, have developed and put into effect a number of policies that are intended to address the issues that are limiting its progress. Every nation, especially those with emerging economies like Ghana, where I am from, has to implement policies effectively to advance. Despite multiple policies put in place by the successive leadership, Ghana's progress has stagnated. What may be the issue?
Keywords: Political Theory and Political Philosophy; Public Policy; Civil Law and Procedure